2009
DOI: 10.3354/dao02135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epizootic shell disease in American lobster Homarus americanus determined using a quantitative disease index

Abstract: The incidence of epizootic shell disease in American lobster Homarus americanus has increased in southern New England, USA, in the last decade, but few longitudinal studies have followed the disease progress in individual lobsters or demonstrated direct effects on mortality or growth. Diseased lobsters were held in the laboratory for 1 yr, and the progression of disease and its effects on molting, mortality, and growth were monitored. A quantitative disease index (QDI) was developed by measuring disease lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
(10 reference statements)
2
25
1
Order By: Relevance
“…The relationship between young-of-the-year and pre-recruit abundance changed dramatically in 1996 (Wahle et al 2009), weakening the relationship between the stages and indicating an increased rate of mortality. Stevens (2009) also found evidence for increased mortality in the laboratory during molting due to complications of ESD.…”
Section: Shell Disease Pastmentioning
confidence: 84%
See 1 more Smart Citation
“…The relationship between young-of-the-year and pre-recruit abundance changed dramatically in 1996 (Wahle et al 2009), weakening the relationship between the stages and indicating an increased rate of mortality. Stevens (2009) also found evidence for increased mortality in the laboratory during molting due to complications of ESD.…”
Section: Shell Disease Pastmentioning
confidence: 84%
“…As temperature also affects growth rates and size at maturity, the interplay between the endocrine system, environmental factors and disease becomes complex. Castro et al (2006) documented decreases in growth increment associated with shell disease from tagging studies, subsequently demonstrated by Stevens (2009) in the laboratory. Inadequate nutrition was also implicated in a paper by Tlusty et al (2008), suggesting that lobster health and condition was compromised during chronic feeding of herring.…”
Section: Shell Disease Pastmentioning
confidence: 96%
“…Additional to the multifactorial nature of shell disease, diseased lobsters are immunodeficient and have lower exoskeleton defences (Allam et al 2009). Based on the innovative tools of a regional disease index and a quantitative disease index, Stevens (2009) clearly demonstrated that epidemic shell disease has significant lethal and sublethal effects. The latter likely results from lower growth rates due to stress of disease.…”
Section: Shell Diseasementioning
confidence: 99%
“…Epizootic shell disease (ESD) is a syndrome associated with the progressive development of irregular, deep lesions on the carapace (Smolowitz et al 2002. Lobsters with signs of ESD exhibit increased mortality in captivity and sublethal effects on growth , Stevens 2009). The high incidence of ESD in southern New England (SNE) has been suggested as a possible causative factor in the observed decline in the SNE lobster stock since 2001 (Howell 2012).…”
Section: Introductionmentioning
confidence: 99%